Integrating Qur'anic Recitation in Local Traditions: A Study of the Kenduri Opat Pekara in Bahgie Bertona Village, Gayo-Aceh - Ismail, Nurjannah; Mulyani, Sri (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2024)
This study aims to explore the application of Surah Al-Mu'awwidzatain within the kenduri opat pekara tradition in Bahagie Bertona Village, Aceh, to understand its ceremonial practices and spiritual significance. The research investigates how the Surah is integrated into local customs, highlighting its role in providing protection and blessings during community rituals. The study employs a qualitative descriptive methodology with a phenomenological approach, focusing on field research. Data were collected through direct observation, in-depth interviews with religious leaders and community members, and document analysis. Triangulation was used to enhance the validity and reliability of the findings. Results indicate that the kenduri opat pekara tradition involves specific preparations believed to appease ancestral spirits, coupled with the recitation of Surah Al-Mu'awwidzatain to invoke divine protection and blessings. The community exhibits diverse interpretations of the Surah's significance, reflecting a complex interplay between Islamic teachings and local cultural practices. The conclusion suggests that the tradition goes beyond the normative use of the Qur'an, integrating it into local customs to strengthen social cohesion and cultural heritage within the Gayo community.